ANALISIS HUKUM PENERBITAN KONOSEMEN DALAM PENGANGKUTAN BARANG MELALUI MODA ANGKUTAN LAUT: LEGAL ANALYSIS OF CONSUMER ISSUANCE IN TRANSPORTATION OF GOODS THROUGH SEA TRANSPORTATION MODE - Agus, Sri Wahyuni; Kamsilaniah; Tira, Andi (Faculty Of Law Bosowa University, 2021)
This thesis aims to determine the process of issuing the bill of lading at PT. Samudra Indonesiaand the legal consequences in the process of issuing bill of lading through sea transportation.Themethod used in writing this final report is a normative-empirical method, the data used isprimary data, namely data obtained by direct interviews with PT. Samudra Indonesia Makassarbranch and secondary data obtained from literature/books, documents and laws andregulations.The results of this study indicate the publishing process Bill of Lading(consignment). In the implementation of issuing the Bill of Lading, the Shipper places an orderfor the ship (booking space), makes Shipping Instructions (SI), Shipping Instructions are thensent to the Shipping Company to do a Stuffing Report, after doing a Stuffing Report publishingDraft Bill of Lading, Shipping Line and Shipper represented by PT. Samudra Indonesia'scorrection has been completed and it is correct that the Bill of Lading has been issued. The legalconsequences in the issuance of this bill of lading are the birth of rights and obligations on theagreed agreement, namely,the carrier binds to carry out the safe transportation of goods orpeople from a certain destination, while the sender binds himself to pay the cost of transportationand the expeditor is an intermediary who is willing to serve the transportation of goods and isresponsible for ordering transport, as for the consequence of not carrying out the obligation tocause a default, namely the party the defaulter compensates for the loss to the aggrieved party.